Review of Alexander Kitroeff, The Greeks and the Making of Modern Egypt; and Angelos Dalachanis, The Greek Exodus from Egypt: Diaspora Politics and Emigration, 1937–1962 - Viscomi, Joseph John (Historein, 2023)
Review of Alexander Kitroeff, The Greeks and the Making of Modern Egypt. Cairo: American University in Cairo Press, 2019. 256 pp; Angelos Dalachanis, The Greek Exodus from Egypt: Diaspora Politics and Emigration, 1937–1962. New York: Berghahn, 2017. 288 pp.